Reward Reward as an Innovative Strategy Increasing Efforts to Brush Teeth Properly From Children to Families - Idaryati, Ni Putu; Rahina, Yudha; Agung, I Gusti Ayu Ari; Pratama, I Wayan Agus Wirya (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Dental and oral health of children in Indonesia remains concerning. In children aged 12 years, the prevalence of cavities reaches 76%. Motivation is closely related to efforts to maintain dental and oral health. There are various things that may be done to increase motivation including providing rewards. A reward is the recognition given to someone for something they have accomplished. Stimulating students' intrinsic motivation can be achieved by offering rewards. The purpose of this research is to examine of rewards as an innovative strategy for increasing efforts to brush teeth properly from children to families. Methods: This study is observational design with a one-group pretest-posttest using questionnaire and video instruments. The questionnaire contains questions related to brushing teeth properly. The research respondents consist of 106 school children from SD Saraswati 3 Denpasar. School children were also assigned to create videos of brushing their teeth together with their families. Rewards were given to three schoolchildren who demonstrated proper tooth brushing with their families. Data analysis used wilcoxon signed rank test to see the difference between pretest-posttest results after reward. Results and Discussions: Based on the research findings, there are significant changes in children's behavior in brushing their teeth properly. Children's behavior showed significant differences before and after the reward (p<0.05). Providing rewards during oral health education sessions children's interest increases. This is a positive method that has a beneficial impact on maintaining oral health, especially within the family. Conclusion: Appropriate rewards can enhance school children motivation to brush their teeth correctly. Children can play an important role in maintaining and raising awareness of the importance of brushing their teeth properly and correctly which can improve dental and oral health among their families